3351 Research training and career development in junior investigators at a multi-institutional CTSA - Gardner, Jachael (J Clin Transl Sci, 2019)
OBJECTIVES/SPECIFIC AIMS:. The study aims to understand the characteristics of junior investigators who are supported by the CTSI, their knowledge of CTSI services and resources, as well as the perceived effectiveness of CTSI research training and career development. The primary outcome is scientific productivity that enhances career development and promotion. The secondary outcome is to inform and improve CTSA research training and career development, not only for the UCLA CTSI hub but also for the CTSA Program nationally. METHODS/STUDY POPULATION:. The study sample includes post-doctoral and junior investigators who have received UCLA CTSI support between 2011 and 2017 (n=319). These junior investigators conduct research at our four partner sites (UCLA-Westwood, Cedars-Sinai Medical Center, The Los Angeles Biomedical Research Institute at Harbor-UCLA Medical Center, Charles R. Drew University of Medicine and Science). The CTSI administered the LSAS and the Career Development module in 2018 using Qualtrics, a subscription software for collecting and analyzing survey data. In order to reduce the burden on the survey respondents, the survey team pre-populated their previously reported publication in the Qualtrics survey system. Qualtrics sends customized email invitations containing a link to start the LSAS survey and subsequently automated sequences of reminder messages for non-responders and partial completers. The survey team initiated telephone call-backs and engaged partner site leaders to achieve a high response rate. RESULTS/ANTICIPATED RESULTS:. Preliminary results show a response rate of 83% (n=264). Respondents include K-to-R workshop participants (n=192), core voucher co-investigators (n=38), Training Program in Translational Science (TPTS) trainees (n=82), and junior investigators who participated in two or more of these activities (n=48). Trainee characteristics include degree, gender, and partner site location. The distribution of advanced degrees among the junior investigators include: PhD (29%), MD (55%), MD/PhD (13%), or other degree (3%). Forty-four percent (44%) respondents are male and 56% are female. Seventy-two percent (72%) have a primary appointment at UCLA-Westwood, while 28% have academic appointments at the partner institutions. Twenty-five percent (25%) received CTSI research training and 49% received CTSI career development support. Regarding scientific productivity, 58% reported having at least one peer-reviewed publication and 29% reported subsequent grant funding. DISCUSSION/SIGNIFICANCE OF IMPACT:. We are in the process of identifying the predictors of scientific productivity and the characteristics of the junior investigators most significantly correlated with productivity using multiple logistic regression analysis. We will analyze qualitative responses to examine the facilitators and barriers to conducting research at the CTSI and explore ways to improve administrative and clinical research processes. The significance of this research is to inform research training and career development programs within our CTSA hub and the CTSA Program nationally.